Healing the Feminine Mind/Body Split through Spiritual Performance - Ruff, Chelsea (My University, 2010)
In Nalo Hopkinson's novels Brown Girl in the Ring and Midnight Robber, the female protagonists, Ti-Jeanne and Tan-Tan, are forced by the patriarchy to live in uncivilized areas. The danger of living in such areas requires these protagonists to work much harder to satisfy their physical needs, including food, water, and safety. Because these protagonists must spend the majority of their time satisfying their physical needs, their mental halves suffer from neglect, creating a mind/body split. The protagonists in these two novels attempt to heal their mind/body splits with the help of spirit guides. Both Ti-Jeanne and Tan-Tan take on the identity of their spirit guides through their performances of dances and speeches. This adoption of the spirit guides' identities helps to heal the mind/body split, which then allows characters to rise above the reach of the oppressive patriarchy, a government controlled by men, and subsequently become empowered.
Keywords: Hopkinson, Nalo; Feminism; Feminist psychology; Dualism; Guides - Spiritualism